2018
DOI: 10.1159/000490861
|View full text |Cite
|
Sign up to set email alerts
|

Disorder of Sexual Development in a Mare with an Unusual Tentative Mosaic Karyotype: 63,X/64,Xdel(Y)

Abstract: The present report describes a 4-year-old Trakehner mare which was referred to the clinic for a breeding soundness evaluation. Clinical, histological, and postmortem examination revealed an underdeveloped genital tract, the absence of a cervix uteri, and small inactive ovaries without male gonadal tissue. Blood lymphocyte analysis revealed an unusual mosaic karyotype consisting of 2 cell lines. For the majority of cells (70%), monosomy X (63,X) was observed. The remaining cells (30%) contained 64 chromosomes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…In our study, the XY SRY‐negative karyotype was diagnosed in a mare whose body structure and external reproductive organs did not differ from those of healthy animals, but with undeveloped internal organs and the presence of testicular tissue. This is consistent with reports describing other cases of mares that were 64,XY Sry negative 12,16,19,25,48 …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our study, the XY SRY‐negative karyotype was diagnosed in a mare whose body structure and external reproductive organs did not differ from those of healthy animals, but with undeveloped internal organs and the presence of testicular tissue. This is consistent with reports describing other cases of mares that were 64,XY Sry negative 12,16,19,25,48 …”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with reports describing other cases of mares that were 64,XY Sry negative. 12,16,19,25,48 In our study, we identified, for the first time, a balanced reciprocal translocation between chromosome 1 and the X chromosome. Unlike in other livestock species, translocations in horses are rare, but as in other species, sustainable translocations cause infertility in both mares and stallions due to recurrent early embryo loss (REEL), which is the loss of embryo between conception and 40-60 days of gestation.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Later, B u g n o -P o n i e w i e r s k a et al [5] reported about a case of sex chromosome mosaicism 64, XX/65, XXY/66, XXYY in a mare. The main difference between mosaicism and chimerism is that mosaicism is a condition when cell lines are derived from one embryo and are produced by unbalanced sister chromosome velopment -DSD -with sex reversal) [16]. Animals phenotypically appear female, but the karyotype corresponds to males [15].…”
Section: Discussionmentioning
confidence: 99%